Gracilariopsis lemaneiformis Polysaccharide Attenuates D-Galactose–Induced Aging of Mice by Regulating Oxidative Stress and Gut Microbiota - Zhang, Zhongshan; Li, Xinyue; Xu, Xiaogang; Mao, Genxiang; Sun, Xue; Xu, Nianjun; Wang, Xiaomei (Frontiers in Marine Science, 2022)
Gracilariopsis lemaneiformis polysaccharide (GP) exerted protective effects in an aging mouse model administered with D-galactose, and its mechanism was revealed. GP increased the activity of antioxidant enzymes, reduced malondialdehyde levels in the brain and serum, alleviated D-galactose–induced damage to the liver, and ameliorated mild cognitive impairment. Abundance of the gut microbiota differed significantly between GP and control groups. GP alleviated liver and brain injuries by regulating oxidative stress and modulating the composition and metabolism of the gut microbiota.